Die Register Innocenz' III. 15. Jahrgang (1212/1213). Texte und Indices - Sommerlechner, Andrea (Verlag der Österreichischen Akademie der Wissenschaften, 2022)
The fifteenth volume of the critical edition of pope Innocent III's chancery-registers is containing 242 letters addressed to recipients all over Europe and in the Middle East. In this year of the pontificate, the organization of the Church in The Latin Empire, the war against muslims in Spain and in the East and against heretics in Southern France are main topics constantly recurring in the Pope's letters. The register of Innocent's fifteenth year of pontificate is one of the four volumes transmitted not as original but as a copy written at the Curia in mid-14th century and as print published in the 17th century.